Switching position-torque control system for increasing servo PMDC positioning precision in presence of intense external disturbance loading. (September 2021) - Homaeinezhad, M.R.; Farzannasab, M.
Highlights: Development of PMDC machine position tracking controller for rapid compensation of strong and impulsive disturbance loads. Applicability of PBTC for high-precision servo applications of PMDC machines without requirement to complicated electronics. Analytically proven robustness and asymptotic stability of PBTC system in discrete-time. A low-cost state-of-the-art technique in the field of high-precision rotary actuation and transduction systems. Abstract: The overall performance of servo Permanent Magnet DC (PMDC) machines can be gravely undermined when the machine is prone to strong external disturbances and uncertainty in modeling parameters. Additionally, this effect will be compounded if the PMDC machine is expected to track a low-frequency desired trajectory. The main cause of this phenomenon lies in the third-order differential relationship between control voltage and position and this will inevitably result in a slow convergence of the tracking error to zero. On the other hand, the relationship between PMDC torque and control voltage is of first-order which, from a control point of view, can bear the meaning of the presence of the possibility of a faster response for a torque tracking process. In this study, primarily, a discussion is held on the position control algorithms of DC motors that illustrate robustness against external disturbance. The studied controllers have been compared based on their structure (single loop or cascade structures) and consequently, with respect to their shortcomings and advantages, a Discrete-Time Sliding Mode Control (DTSMC)-based tracking control algorithm named as Position-Braking Tracking Control (PBTC) is introduced in which the servo PMDC is controlled in position tracking mode when motoring/reverse motoring property is expected. Similarly, the PMDC is controlled in torque tracking mode when braking/reverse braking property is announced to be required. Activation and the necessity of position or torque tracking is determined by the execution of a simple analysis on the position and torque tracking errors. The proposed DTSMC-based PBTC system is applied to an industrial servo application and the performance improvements are demonstrated. Obtained results indicate that for low-frequency desired position trajectories, transient response of PBTC is more precise relative to single mode DTSMC-based position tracking control.